Mikromorfologi dan Perkecambahan In Vitro Biji Anggrek Endemik Sulawesi: Phalaenopsis venosa Shim & Fowlie - Rahayu, Eka Martha Della; Winda Utami Putri; Fitri Fatma Wardani; Lydia Natalia Endewip (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Phalaenopsis venosa Shim & Fowlie, one of Sulawesi’s endemic orchid species, is threatened to extinction, hence require conservation efforts. Capsules of P. venosa were harvested six months after pollination. Seeds were stored in the freezer at -4 °C for nine months. Micromorphology was observed using a light microscope OPTIKA M-699. The seeds of P. venosa were 91.99±17.73 µm long and 20.64 ±4.34 µm wide, containing embryos 52.27±12.13 µm long and 16.72±3.42 µm wide, and the air space was 13.25%±11.65%. The experiment used a completely randomized design with one factor, namely six media and six replications. Media for germination including modified Hyponex (HS), modified Vacin & Went (mVW), modified Knudson’s C (mKC), Knudson’s C (KCA), Murashige & Skoog half concentration (1/2MS), and Murashige & Skoog (MS). The highest germination rate at 12 weeks after planting (12 WAP) was found in HS (70.52%). The average number of seeds germinating in HS at 12 WAP was 14.35 seeds, but the development of protocorms was slower compared to 1/2MS, which showed the development of rhizoid and leaf primordia. This is due to the higher nutritional content of 1/2MS compared to HS. Keywords: germination media, Orchidaceae, seed micromorphology